Cultural adaptation and preliminary validation of the Flexibility Scale for Spain - Rodríguez-Armendariz, Ekaine; Petrolini, Valentina; Martín-González, Isabel; Juncal-Ruiz, Maria; Vicente, Agustín (Frontiers in Psychiatry, 2024)
Background: Individuals exhibit varying degrees of flexibility depending on different characteristics, conditions, and diagnoses. The Flexibility Scale is a comprehensive informant-report measure used to assess multiple aspects of flexibility in autistic and non-autistic children and youth, with an emphasis on cognitive aspects. This tool has not been adapted nor validated for use in Spain.In this paper we aim to provide a culturally adapted and validated version of the Flexibility Scale for Spain. We detail the procedure followed by our research team to obtain a cultural adaptation of the scale for Spain, including forward and back translations, cognitive interviews, feedback from experts, and preliminary validation. Our participants in the validation process were 75 autistic and 39 typically developing children and adolescents between the ages of 6 and 17.We reached a culturally adapted and preliminary validated version of the Flexibility Scale for Spain (Escala de Flexibilidad).We make the scale available to researchers and practitioners working in Spain. This contributes to laying the groundwork for further testing and adaptations in Spanish-speaking countries and communities worldwide.